Negotiating Bad Karma Case Study: Lived Experiences on Employment Process of Disability in Lao PDR - Phanthalangsy, Sitthiphong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The fact that three (5, 8, and 10) of the 17 SDGs directly or indirectly relate to the necessity for promoting the inclusiveness of individuals and groups across all spheres of society as an essential prerequisite for societal and global harmony emphasizes its importance in achieving the objectives of the SDGs 2030. The promotion of inclusiveness for people with disabilities had long been a complex issue, especially in developing nations. Physically disabled people in Laos are marginalized in all essential domains. The employment domain is a vital domain that significantly determines the quality of a person. Given the foregoing, this study aims to contribute towards bridging this gap by adopting a life history approach to analyze the challenges and the negotiation process of the physically disabled people in the labor market of Laos with a focus on negotiating Buddhist karma and employment. The main results were that participants strongly agreed that Buddhist karma is causing more harm than benefits for the majority of the disabled population in modern Laos concerning employment prospects and employment practices. Participants came up with their unique ways of navigating themselves in the labor market, some were more substantially more successful than others.